Arthritis Associated with Low Dose Methimazole Therapy: A Case Report: Arthritis associated with Methimazole therapy - Khaledi, Mohammad; Aminorroaya, Ashraf; Rezvanian, Hasan (Iranian Journal of Pharmaceutical Sciences, 2018)
Here in this paper, we report a 31-year-old case admitted with symptoms of hyperthyroidism that was then diagnosed with Grave's disease (GD) and underwent treatments with a low dosage of methimazole (10 mg/day). 20 days after treatments initiations, she developed antithyroid arthritis syndrome. This patient experienced arthritis and arthralgia in at least 4 joints. All autoimmune and microbiologic evaluations were negative. She was then completely recovered without any sequelae within 4 days after drug withdrawal. Arthritis as an adverse effect of methimazole is a major and life-threatening adverse effect which requires immediate drug discontinuation and hospitalization. Contrary to what has been thought. We declare that this adverse effect might not be dose dependent as our case developed arthritis following methimazole therapy with a very low dosage (10 mg/day). The aim of the current case report is to help other physicians in order to diagnose and treat possible cases of antithyroid arthritis syndrome.